2018
DOI: 10.5005/jp-journals-10024-2404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Maxillary Expansion on Condyle–fossa Relationship in Growing Patients

Abstract: Aim: This study tests whether rapid maxillary expansion (RME) exerts long term effects on interglenoid fossa distance and condyle fossa relationship. Materials and methods:Consecutive growing patients aged 8 to 13 years were allocated either to the RME group or control group. Cone-beam computed tomography was performed at baseline and at 6 months. Specific software was used to determine fixed landmarks. Multivariate Analysis of Covariance (MANCOVA) models were used, with time by group interaction, using age as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…One article reported that RME modified joint space and condylar postion, promoting greater spatial symmetry between the crossbite and non-crossbite 25 side. Three articles found that the RME was able to change the individual condylar position 27,28,30 and joint space, 26,29 maintaining the symmetric relationship between the condyles. 26,27,29 There was no evaluation of intercondylar symmetry in the measures used by McLeod et al (2016), 28 who observed no alteration of the condylar position in the glenoid fossa in individuals.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…One article reported that RME modified joint space and condylar postion, promoting greater spatial symmetry between the crossbite and non-crossbite 25 side. Three articles found that the RME was able to change the individual condylar position 27,28,30 and joint space, 26,29 maintaining the symmetric relationship between the condyles. 26,27,29 There was no evaluation of intercondylar symmetry in the measures used by McLeod et al (2016), 28 who observed no alteration of the condylar position in the glenoid fossa in individuals.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Of these, one study was eliminated because it was a protocol proposal to be followed in future studies, 15 one for evaluating pre-and post-intervention changes through gypsum models and bite registration, 16 one for assessing condylar change by means of zonograms, 17 and five studies were excluded since they examined patients who underwent slow maxillary expansion. 10,[18][19][20][21] Therefore, seven articles from the systematic search were included for qualitative analysis; [22][23][24][25][26][27][28] as well as one record found by hand search (n ¼ 1); 29 totaling eight articles included in this review ( Table 1). A quantitative analysis was not feasible given the heterogeneity in the methodology of the selected articles.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
See 3 more Smart Citations